The Use of Risperidone in Behavioral and Psychological Symptoms of Dementia: A Review of Pharmacology, Clinical Evidence, Regulatory Approvals, and Off-Label Use - Yunusa, Ismaeel; El Helou, Marie Line (Frontiers in Pharmacology, 2020)
With the growing elderly population in developed countries, dementia represents a global health challenge. In addition to memory loss, dementia often results in severe behavioral and psychological changes where pharmacological treatments might be considered in addition to non-pharmacological strategies for optimal symptomatic control. Risperidone, the second oldest atypical antipsychotic, has been widely used off-label for the treatment of behavioral and psychological symptoms of dementia including agitation, aggression and psychosis. Several studies have indicated that risperidone offers a modest and statistically significant efficacy in the clinical setting. However, in the past decade, safety concerns related to the use of risperidone in the elderly population due to increased risk for cerebrovascular adverse events and death emerged. As clinical guidelines suggest, in situations where an older adult is threatening to harm himself or others, pharmacological treatments might be considered when nonpharmacological treatments fail in severe dementia, risperidone was approved in some countries but not in the United States. This article reviews risperidone’s pharmacological activity, clinical efficacy and safety and marketing approval and off-label use in BPSD.